Advokasi Perempuan Korban Kekerasan Melalui Model Clinic Legal Education - Aroma Elmina Martha (Fakultas Hukum Universitas Islam Indonesia, 2020)
The increase in criminal acts of women's violence during the Covid-19 pandemic has an impact on the difficulty of access to advocacy, on the contrary, the provision of advocacy service institutions is limited plus the lack of legal aid resources. This paper aims to analyze the typology of women victims of violence in using access to advocacy rights and fulfillment of advocacy for women victims violence through the legal education clinical model. The theoretical basis used in this paper is the theory of women's advocacy and clinical legal education theory. By using a normative approach through tracing primary legal materials, this paper shows that first, there are at least six groups of women in understanding the knowledge of access to advocacy, namely groups of women who do not know their right to protection; women's groups see their rights but don't know where to go to access justice; women's groups who know where to go and have the right to access justice but do not have the financial means or capacity to access justice; A group of women who learned helpness and apathy with this condition accepted them as victims; a group of women who fear that perpetrators will apologize if they seek legal help. 6. Women's groups who have high awareness and seek to find out solutions to the violence they experience. Second, efforts to fulfill women's advocacy rights through the development of a legal education clinical model can be achieved with a live client clinic model and a street law clinic with a basic curriculum model based only on law but on a sense of community justice.